Last Mile Delivery: Research Trends Using Bibliometric Analysis - Purba, Heddry; Hutabarat, Francis (Amkop Management Accounting Review (AMAR), 2025)
This study aims to explore and analyze research trends in the field of Last Mile Delivery (LMD) by systematically mapping the direction of scientific studies over the past twelve years. This study also aims to identify future research agendas in the field of LMD based on topic trends and geographical distribution. A bibliometric approach was used to review academic literature sourced from Google Scholar and Scopus during the period 2013–2024. The analysis techniques employed included citation analysis, co-citation analysis, and keyword co-occurrence using VOSviewer software. This study analyzed publication data by time and geographical region, and examined the interrelationships among authors, institutions, and countries. The results show fluctuations in the number of publications each year, with a peak in 2019. A total of 186 documents were found, involving 494 authors from 9 countries, with the United Kingdom and the United States being the most prominent. In the last four years, publication trends have shown a significant decline. Theme cluster visualization reveals a diverse range of topics, including sustainability, technological innovation, consumer behavior, and urban distribution systems. This study provides theoretical contributions to understanding the scientific landscape of LMD and serves as a practical reference for policymakers and logistics practitioners in developing more adaptive and efficient final-mile delivery strategies. Further research is proposed to expand the scope of local and theoretical contexts.